Map kinase signaling as therapeutic target for neurodegeneration. (October 2020) - Ahmed, Touqeer; Zulfiqar, Abida; Arguelles, Sandro; Rasekhian, Mahsa; Nabavi, Seyed Fazel; Silva, Ana Sanches; Nabavi, Seyed Mohammad
Graphical abstract: Abstract: Aging is known to be one of the major risk factors in many neurodegenerative diseases (ND) whose prevalence is estimated to rise in the coming years due to the increase in life expectancy. Examples of neurodegenerative diseases include Huntington's, Parkinson's, and Alzheimer's diseases, along with Amyotrophic Lateral Sclerosis, Spinocerebellar ataxias and Frontotemporal Dementia. Given that so far these ND do not have effective pharmacological therapies, a better understanding of the molecular and cellular mechanisms can contribute to development of effective treatments. During the previous decade, the data indicated that dysregulation of MAP kinases [which included c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1 and 2 (ERK1/2), and p38] are associated with several stages of the inflammatory process which in turn contributes to age-related neurodegenerative diseases. This evidence suggests that control of inflammation through regulation of MAP kinase could be a worthwhile approach against neurodegenerative diseases. In this review we summarize the pathways of MAP kinase signal transduction and different pharmacological inhibitors that can be used in its modulation against ND.